2020
DOI: 10.1002/mpr.1814
|View full text |Cite
|
Sign up to set email alerts
|

Testing adults by questionnaire for social and communication disorders, including autism spectrum disorders, in an adult mental health service population

Abstract: Objectives Autism is difficult to identify in adults due to lack of validated self‐report questionnaires. We compared the effectiveness of the autism‐spectrum quotient (AQ) and the Ritvo autism–Asperger's diagnostic scale‐revised (RAADS‐R) questionnaires in adult mental health services in two English counties. Methods A subsample of adults who completed the AQ and RAADS‐R were invited to take part in an autism diagnostic observation schedule (ADOS Module 4) assessment with probability of selection weighted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 24 publications
3
34
0
1
Order By: Relevance
“…Whilst there is some support for the use of the RAADS-R in terms of test-retest reliability [ 25 ] and facilitating referrals in psychiatric and psychology services (albeit not in isolation) [ 26 ], as well as evidence of its ability to differentiate between ASD and eating disorder cohorts [ 27 ], other research supports what we have found here. For instance, Sizoo and Horwitz [ 17 ] examined the predictive validity of several assessments commonly used as screening tools in ASD clinical practice, including the AQ and RAADS-R.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Whilst there is some support for the use of the RAADS-R in terms of test-retest reliability [ 25 ] and facilitating referrals in psychiatric and psychology services (albeit not in isolation) [ 26 ], as well as evidence of its ability to differentiate between ASD and eating disorder cohorts [ 27 ], other research supports what we have found here. For instance, Sizoo and Horwitz [ 17 ] examined the predictive validity of several assessments commonly used as screening tools in ASD clinical practice, including the AQ and RAADS-R.…”
Section: Discussionsupporting
confidence: 82%
“…This leads the authors to advice that the cutoff score of >65 is too low and should not be used. Alternatively, they recommend a higher threshold score of >120 [ 26 ]. Also, there is an argument that the RAADS-R is not a sensitive enough measure to detect milder variations of ASD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study (also known as the SPRINT study (The Prevalence of S ocial Communication PR oblems in Adult Psychiatric In pa T ients)) will employ a multiple-phase cross-sectional design for participants without ID, and a single-phase design for participants with ID (figure 1). A multiple-phase approach to studying ASD prevalence has been used in several previous similar studies,12 19 39 as the ASD clinical interview-based diagnostic assessments are both time and resource intensive 40. Thus, a multiphase approach permits coverage of a larger study population per unit of resource.…”
Section: Methods and Analysismentioning
confidence: 99%